Media Representation Of Muslimah Influencer In Frame Of Dakwah - A'isyah A'isyah; Rezki Putri Nur Aini (LPPM IAI Hasanuddin Pare-Kediri, 2020)
Abstract This article investigates the extent of the role Muslimah in using new media as influencers who have a preaching orientation to desire improve Islamic ideology and thought by combining secularism and fundamentalism which are in fact is contradictory. These Muslim influencers are supported by positions that can influence especially urban society and middle-class millennials. Researchers use ethnographic oniline or netnographic approaches where modern culture by puritanical religion and attitude shows that modern Islamic religion with evidence can adjust the times and dispel the notion of Islam as a terror religion. Media representations of Muslim influencers are carried out in different ways, for example Ria Ricis (@ riaricis1795) with representations of women who can be free will, Anisa Rahma (@ anisarahma_12) with representations of women migratory motivators, Wafiq Malik (@wafiqmalik) with representation of domination of the existence of veiled women and Gita Savitri Devi (@gitasav) with representation of high intellectual women. This fourth is always showing up as form to resistance Islamic claims about curbing women by taking public sympathy in relation to the cultural dakwah of the Tarbiyah movement but also having an impact on socio-economic benefits. Keywords: Muslimah Influencer, Representation, Media, Resistance